2017
DOI: 10.22495/cocv14i3art3
|View full text |Cite
|
Sign up to set email alerts
|

The impact of corporate governance mechanisms on financial reporting transparency

Abstract: Corporate governance has been raised as one of the most important issues among the international business environment since the beginning of the twenty-first century. At first, corporate governance basic principles focused on firm’s strategies and the rights of their shareholders but these principles has been changed into the rights of all stakeholders and society through researchers new viewpoints. Although corporate governance codes and regulations are different in various countries, there is a common unanim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…and adjusted R-squared was improved up to 15% (Approx.). The AUDIT and FEMALE both have a significant impact on OT at a 5% significant level (Alkhatib and Marji, 2012;Kohansal et al, 2017;Liu et al, 2016;Torea et al, 2016;Zaheer, 2013). It reveals that 15% of the impact is created by AUDIT and FEMALE as the variables which have been specified by the model and the other 85% of the impact is created by other variables which have not been specified in the model.…”
Section: Source: Results From the Cross-sectional Data Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…and adjusted R-squared was improved up to 15% (Approx.). The AUDIT and FEMALE both have a significant impact on OT at a 5% significant level (Alkhatib and Marji, 2012;Kohansal et al, 2017;Liu et al, 2016;Torea et al, 2016;Zaheer, 2013). It reveals that 15% of the impact is created by AUDIT and FEMALE as the variables which have been specified by the model and the other 85% of the impact is created by other variables which have not been specified in the model.…”
Section: Source: Results From the Cross-sectional Data Analysismentioning
confidence: 99%
“…based on the existing studies, it also found that board independence has no significant impact on CT (Liu et al, 2016;Torea et al, 2016). Kohansal et al (2017) revealed that board size has no impact on financial reporting transparency. Torea et al (2016) found that CEO duality has no impact on transparency.…”
Section: Source: Results From the Cross-sectional Data Analysismentioning
confidence: 99%
See 3 more Smart Citations